Species of the genus Mallinella Strand, 1906 (Araneae: Zodariidae) from Hainan Island, China BAO-SHI ZHANG, FENG ZHANG & PING CHEN (China) - Zhang, Bao-Shi; Zhang, Feng; Chen, Ping (Zootaxa, 2011)
Four species of the spider genus Mallinella are reported from Hainan Island, China, including one already described species: M. hainan Song & Kim, 1997, and three new species: M. digitata sp. nov. (male, female), M. rectangulata sp. nov. (male, female) and M. obtusa sp. nov. (male).